Carbon monoxide binding kinetics in "capped" porphyrin compounds. - Rose, E J (1982)
The rate constants for CO binding to the five-coordinate ferrous iron complexes of 5,10,15,20-[pyromellitoyl(tetrakis-o-oxyoxyphenyl)]porphyrin and 5,10,15,20-[pyromellitoyl(tetrakis-o-oxypropoxyphenyl)]porphyrin have been measured and compared with the corresponding rate constants for other hemes and hemoproteins. The second-order rate constant is independent of cap size and is comparable to that of high-affinity state hemoglobin (k5 approximately 4 X 10(6) M-1s-1). Therefore, these capped porphyrins provide no steric hindrance to CO binding. In addition, a kinetic scheme involving an unusual seven-coordinate porphyrin species is described.